PHYTOCHEMICAL STUDY OF ASHODHIT AND SHODHIT GUNJA (ABRUS PRECATORIUS) PERICARPS. - SINGH GAUTAM, DEV NATH (Innovare Journal of Life Sciences, 2018)
Objective: The aim of the present research work was to carry out the effect of Shodhana on Gunja pericarps by using advanced analytical tools. It is attributable to the plant Abrus precatorius L. belonging to family fabaceae having three types of plants white, red and black seeds. Methods: Three varieties of Gunja seed's pericarps were subjected for Swedana in cow's milk and Kanji. The Shodhit and Ashodhit Gunja pericarps were subjected for analytical parameters. For the establishment of the effect of Shodhana, the percentage of total ash, acid insoluble ash, total protein and successive extractives were carried out on Ashodhita and Shodhita pericarps. Results: The study showed that the percentage of total ash was reduced in Shodhit samples as compared to Ashodhit samples. The percentage of hexane and chloroform extractives in milk Shodhit pericarps were increased in all the samples, however, no significant variations were observed in Kanji Shodhit samples. On the contrary, the percentage of alcohol and water extractives value decreased in Shodhit samples. Conclusion: It was found that most of the phytochemicals were decreased in Shodhit samples of Kanji as compared to cow milk.